Desain Pengembangan Kit Praktikum Sederhana Pembentukan Bayangan pada Cermin Cekung - Helda Noer Ramadhani; Puspita Prima Tri Handayani; Bayu Setiaji (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2022)
This research aims to develop a simple practicum learning medium for shadow formation on a decent concave mirror so that it can be used as an interactive learning medium to help students understand the material regarding Optics geometry. This research uses addie methods, namely Analysis, Design, Development, Implementation, and Evaluation. The product of this study is in the form of a simple practicum kit for shadow formation on concave mirrors that have been assessed and declared feasible based on the results of questionnaire analysis that has been filled by physics jurdik respondents. The feasibility of this simple practicum kit is seen from the average score with the ideal standard standard calculation (SBi). The results showed that the simple practicum kit of shadow formation on concave mirrors had an average value of all aspects of 3.4 with a very decent category. It can be concluded that the simple practicum kit of shadow formation on concave mirrors is very suitable for use as one of the learning media in geometric optical materials.